Ensuring good governance and preventing corruption in the planning of major sporting events: Open issues - Wolfgang Maennig (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2015)
International sports will have to strengthen their efforts to exclude persons with morals in conflict with their sports. IOC and FIFA should mirror their top ambitions in athletic and financial areas by similarly leading ambitions to serve human mankind more generally. To encounter critiques that the organizing of major sporting events are "elitist actions" IOC and FIFA should declare ex-ante referenda as a precondition for bidding. In order to reduce the funds available for corruption, the role of public finance in major sporting events should be overthought. At least broadcasters under public law public should be excluded from the bidding for TV. FIFA and other sporting federations should make public their payments to member federations etc and the underlying decision criteria.
Keywords: L83; 330; corruption; FIFA; good governance; major sporting events; referenda; public finance